2002
DOI: 10.1111/1467-9493.00115
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape Ecology Approach to Assessing Development Impacts in the Tropics: A Geothermal Energy Example in Hawaii

Abstract: Geographic information systems (GIS) are increasingly being used in environmental impact assessments (EIA) because GIS is useful for analysing spatial impacts of various development scenarios. Spatially representing these impacts provides another tool for landscape ecology in environmental and geographical investigations by facilitating analysis of the effects of landscape pattern on ecological processes and examining change over time. Landscape ecological principles are applied in this study to a hypothetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…This study showed that the ecological effect of condensed versus dispersed development was important in Hawaii because of problems posed by the invasion of exotic species. The loss of a native plant canopy can result in a greater number of introduced birds at the expense of the native ones (Griffith et al 2002). Despite British Columbia's more diverse array of ecosystems, which support a greater variety of plant and animal species, similar ecological effects could be experienced here.…”
Section: Geothermal Energy and Ecological Footprintmentioning
confidence: 88%
See 2 more Smart Citations
“…This study showed that the ecological effect of condensed versus dispersed development was important in Hawaii because of problems posed by the invasion of exotic species. The loss of a native plant canopy can result in a greater number of introduced birds at the expense of the native ones (Griffith et al 2002). Despite British Columbia's more diverse array of ecosystems, which support a greater variety of plant and animal species, similar ecological effects could be experienced here.…”
Section: Geothermal Energy and Ecological Footprintmentioning
confidence: 88%
“…Although geologists may characterize geothermal energy developments as having relatively small footprints, a typical site consists of exploratory wells for numerous temperature gradients to measure subsurface temperature, deep slim-hole wells, several full-diameter wells, areas for the drill rig, a holding pond for water to quench potential well blowouts, a service yard for storage of equipment, and access roads (Griffith et al 2002;Meager Creek Development Corporation 2004). Pipelines and vessels are required to transport steam from the well-heads to the power plant, and transmission lines are needed to transmit the produced power from the power plant to substations (Meager Creek Development Corporation 2004).…”
Section: Geothermal Energy and Ecological Footprintmentioning
confidence: 99%
See 1 more Smart Citation
“…[P i ln(P i )] P i : percentage of class; n: number of landscape classes It measures the landscape diversity (O'Neill et al, 1988;Viedma and Melia, 1999) Contagion index CONT = 1 + m i=1 n j=1 P ij ln(P ij )/2 ln(n) P ij = P i P j/i , P j/i = m ij /m i P ij : probability that a patch of ith class adjacent to jth class; m: patch number of ith class; n: number of landscape classes; P i : randomly chosen probability; P j/i: conditional probability A large CONT reflects the clumping of large contiguous patches while a small CONT value reflects a landscape that is dissected into small patches (O'Neill et al, 1988;Turner, 1990;Li and Reynolds, 1993;Griffith et al, 2002) Mean Although grassland was the dominant class in both Houston and Daqing, it experienced a rapid decrease in its mean patch area in these two cites. In Houston, it decreased from 0.12 km 2 /each to 0.01 km 2 /each in 1990 and 2000.…”
Section: Quantitative Description Of Landscape Dynamicsmentioning
confidence: 99%
“…Conversely, remote sensing has facilitated extraordinary advances in analyzing urban vegetation coverage changes by its real-time and wide coverage features, which has become a significant measurement for monitoring the urban ecological environment. In recent years, different ecological problems have appeared in urban regions, and some landscape ecology approaches to combining remote sensing have been applied to explore the urban landscape pattern and its change process [6][7][8][9]. Tang et al linked spatial pattern and biophysical parameters of urban vegetation by multi-temporal Landsat imagery [10].…”
Section: Introductionmentioning
confidence: 99%